FORMULATION AND QUALITY EVALUATION OF CORDIAL BASED ON MARKISA (PASSIFLORA EDULIS) COMMODITY IN BUKIT KOOR MALAYSIA - Malakiano, Ulna Alayna; Ketaren, Bunga Raya (Institute of Computer Science (IOCS), 2023)
Passion fruit (Passiflora edulis) is a type of fruit that is grown in Malaysia. Yellow passion fruit is more prominent than purple passion fruit in terms of comparison to farmers and users. Some of the nutritional contents found in passion fruit are citric acid, ascorbic acid, niacin, riboflavin, thiamine, iron, carotene, phosphorus, minerals, calcium, fiber, energy, fat and protein. This study aims to evaluate the physichalmical and contrinatrium of passion fruit cordial drink with the addition of sugar, salt and pandan leaves. The analysis carried out is the analysis of pH, TSS (Brix), Color and Sensory Test. The results of the study showed that the passion fruit cordial drink with the treatment of basic passion fruit cordial, passion fruit cordial and salt, passion fruit cordial and pandan and passion fruit cordial with salt and pandan had pH, (2.2; 2.1; 1.8; 1;8), TSS (74%; 70%; 70%; 74%), color (29.6; 27.4; 26.6; 26.5), sensory test color, taste, and overall acceptance.